Gut Mycobiota and Fungal Metabolites in Human Homeostasis - Mogilnicka, Izabella; Ufnal, Marcin (Current Drug Targets, 2019)
Background: Accumulating evidence suggests that microbiota play an important role in host's homeostasis. Thus far, researchers have mostly focused on the role of bacterial microbiota. However, human gut is a habitat for several fungal species, which produce numerous metabolites. Furthermore, various types of food and beverages are rich in a wide spectrum of fungi and their metabolites. Methods: We searched PUBMED and Google Scholar databases to identify clinical and pre-clinical studies on fungal metabolites, composition of human mycobiota and fungal dysbiosis. Results: Fungal metabolites may serve as signaling molecules and exert significant biological effects including trophic, anti-inflammatory or antibacterial actions. Finally, research suggests an association between shifts in gut fungi composition and human health. Changes in mycobiota composition have been found in obesity, hepatitis and inflammatory bowel diseases. Conclusion: The influence of mycobiota and dietary fungi on homeostasis in mammals suggests a pharmacotherapeutic potential of modulating the mycobiota which may include treatment with probiotics and fecal transplantation. Furthermore, antibacterial action of fungi-derived molecules may be considered as a substitution for currently used antibacterial agents and preservatives in food industry.
Keywords: probiotics